IMPACT OF GHG EMISSION FROM PALM OIL MILL EFFLUENTS AND POPULATION GROWTH, GDP PER CAPITA CHANGE, AND THE TECHNOLOGY - Erwinsyah Erwinsyah; Tjipto Djuhartono (UNIVERSITAS INDRAPRASTA PGRI, 2020)
The palm oil sector gives a significant contribution to the Indonesian economy and reached 34.5 million tons or 58 percent of world production in the year 2016. The scientific community agrees that palm oil expansion can contribute to the emission of Green House Gasses, including methane emissions from palm oil mill effluent (POME). The purpose of this research is to develop a model for assessing environmental impacts caused by the production of methane from POME. This study hypothesizes a correlation between the increasing population and changes in their GDP per capita of main palm oil importing countries with changes in Regional GDP in the provinces of Riau, North Sumatra, Central Kalimantan, South Sumatra, and West Kalimantan. The econometric analyses used in this study performed with the Eviews Statistical Data Processing model. Data used for this study was from the year 2010 to the year 2016, taken from the official Indonesian statistics and palm oil statistics. The results of this research include the Indonesian oil palm production for the period 2010-2016, the oil palm and POME production in five provinces mentioned above, forecast Model of POME Production, POME production elasticity, and possible policy intervention on GHG methane emission reduction.